1985
DOI: 10.1073/pnas.82.17.5627
|View full text |Cite
|
Sign up to set email alerts
|

An unusual bovine pancreatic protein exhibiting pH-dependent globule-fibril transformation and unique amino acid sequence.

Abstract: An unusual hitherto unreported protein, extracted in acid from fresh bovine pancreas, has been purified and characterized biochemically. It precipitates in the neutral pH range in the form of uniform double-helical threads, each strand of which is smooth and of uniform diameter, about 7-8 nm. The threads dissolve to a nonviscous solution below pH 3.6 and above pH 9.4, and they reconstitute reversibly in the pH range in between. The monomer in acid has an apparent molecular weight of 17,800 and consists of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 34 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…7, B (PTP) and C (PATP III), shows filaments that were negatively stained with phosphotungstic acid. This procedure, which causes extensive fragmentation of filaments, compares favorably with negatively stained micrographs that appear in the literature (22,23).…”
Section: High Resolution Analysis Of Fibrillar Structures Using Transmentioning
confidence: 67%
See 2 more Smart Citations
“…7, B (PTP) and C (PATP III), shows filaments that were negatively stained with phosphotungstic acid. This procedure, which causes extensive fragmentation of filaments, compares favorably with negatively stained micrographs that appear in the literature (22,23).…”
Section: High Resolution Analysis Of Fibrillar Structures Using Transmentioning
confidence: 67%
“…In both species thread proteins were isolated and shown to be fibrillar by negative staining in the electron microscope (22,23). Purified PSP/lithostathine has been shown to form similar fibrils after tryptic cleavage in vitro (43), and prolonged incubation of PSP, purified by column chromatography, suggested that activation may occur by autoproteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein data bank accession numbers are given after each member. Abbreviations: Reg=regenerating islet-derived; INGAP=islet neogenesis associated protein; PTP=pancreatic thread protein; PAP=pancreatitis associated protein; HIP=hepatocellular carcinoma/intestine/pancreas; PSP=pancreatic stone protein www.intechopen.com pancreatic protein that precipitates at neutral pH in the form of double helical threads and was subsequently identified as a member of the Reg family (Gross, Brauer et al 1985) and 'HIP' (for hepatocellular carcinoma, intestine, pancreas) -a name assigned to a human family member after Lasserre at al. found that it was overexpressed in a proportion of the hepatocellular carcinoma samples they had investigated (Lasserre, Christa et al 1992).…”
Section: Nomenclature and Classification Of The Reg Proteins And The mentioning
confidence: 99%
“…A degraded form. insoluble at pH 7. has been discovered in the ox pancreas and in the human pancreas by Gross and co-workers (34,35 [36], Elisa with a monoclonal antibody as first antibody and a polyclonal antibody as che second antibody [37]), its concentration is constantly decreased in patients presenting with CCP compared co normal controls. This suggests that a decrease of PSP secretion could be responsible for the formation of calcite calculi.…”
Section: Mechanisms Common To Different Forms Of Ccpmentioning
confidence: 99%